1991
DOI: 10.1002/cne.903090408
|View full text |Cite
|
Sign up to set email alerts
|

Peptidergic and serotoninergic innervation of the rat dura mater

Abstract: The peptidergic and serotoninergic innervation of the rat dura mater was investigated by reacting dural wholemounts immunohistochemically with antibodies to calcitonin gene-related peptide (CGRP), substance P (SP), neuropeptide Y (NPY), vasoactive intestinal polypeptide (VIP), and serotonin (5-HT). CGRP and SP innervations of the dura were robust and the patterns of distribution of these neuropeptides were essentially the same. The majority of the fibers were perivascular and distributed to branches of the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
108
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(115 citation statements)
references
References 97 publications
4
108
0
3
Order By: Relevance
“…Histochemical studies by von During et al (1990) and Keller & Marfurt (1991) as well as our recent investigation (Messlinger et al, 1993) revealed that the dura mater encephali of the rat is densely innervated by both substance P and calcitonin gene-related peptide (CGRP) immunoreactive nerve fibres of small diameter suggesting the presence of these neuropeptides within distinct classes of dural afferents. Whereas substance P (as well as neurokinin A) seems to mediate mainly plasma extravasation that can be inhibited by the NK, receptor antagonist, RP 67580 (Moussaoui et al, 1993;Shepheard et al, 1993), it is suggested that CGRP contributes little to this response (Markowitz et al, 1987).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Histochemical studies by von During et al (1990) and Keller & Marfurt (1991) as well as our recent investigation (Messlinger et al, 1993) revealed that the dura mater encephali of the rat is densely innervated by both substance P and calcitonin gene-related peptide (CGRP) immunoreactive nerve fibres of small diameter suggesting the presence of these neuropeptides within distinct classes of dural afferents. Whereas substance P (as well as neurokinin A) seems to mediate mainly plasma extravasation that can be inhibited by the NK, receptor antagonist, RP 67580 (Moussaoui et al, 1993;Shepheard et al, 1993), it is suggested that CGRP contributes little to this response (Markowitz et al, 1987).…”
Section: Introductionmentioning
confidence: 81%
“…Human CGRP itself caused an increase of the basal blood flow without electrical stimulation. Since the dura mater encephali is densely innervated by CGRP immunoreactive nerve fibres (Keller & Marfurt, 1991;Messlinger et al, 1993), it is likely that CGRP-is released from these nerve endings when they are activated by electrical stimulation. The same stimuli probably also release substance P (Edvinsson et al, 1983) that is stored in a smaller proportion of dural nerve fibres (von During et al, 1990;Messlinger et al, 1993) where it may largely be co-localized with CGRP (O'Connor & van der Kooy, 1988), possibly in the same vesicles (Gulbenkian et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In peripheral tissues, CGRP released from perivascular afferents contributes to the development and maintenance of neurogenic inflammation Gamse and Saria, 1986). Meningeal (dural and pial) blood vessels are innervated by a dense network of trigeminal sensory fibers, a major proportion of which contains CGRP (Edvinsson et al, 1987;Keller and Marfurt, 1991;Messlinger et al, 1993). CGRP is released on stimulation from both the peripheral and central processes of these trigeminal afferents Jenkins et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The dura mater encephali is richly innervated by thin a erent nerve ®bres, a minor proportion of which exhibits substance P immunoreactivity (rat: Keller &Marfurt, 1991 andVon DuÈ ring et al, 1990; cat and rat: Messlinger et al, 1993;guinea-pig: Edvinsson et al, 1983). Meningeal a erents originating in the trigeminal ganglion (Mayberg et al, 1984;O'Connor & van der Kooy, 1986;Steiger & Meakin, 1984;Uddman et al, 1989) project mainly to the spinal trigeminal nucleus, where numerous substance P immunoreactive nerve ®bres were found particularly in the substantia gelatinosa (Cuello et al, 1978;Del Fiacco et al, 1983;Pearson & Jennes, 1988;Tashiro et al, 1991).…”
Section: Introductionmentioning
confidence: 99%